Geschlecht und Macht (feministische studien)

Diffeomorphism groups of compact locally polyhedral manifolds - Jakob, Johanna

Beyond Security: A Qualitative Study of Cyber Resilience Across the Software Development Lifecycle in German Organisations - Taaibi, Samira; Kahraman, Emanuel; Berg, Kevin; Dziwok, Stefan (ECIS 2026 Proceedings)
As digital products become increasingly embedded in organisational operations, cyber resilience – the ability to anticipate, withstand, recover from and adapt to cyber disruptions – has become essential. This paper investigates how professionals in German organisations interpret cyber resilience within the software development lifecycle and how socio-technical factors influence its implementation. Drawing on the MITRE Cyber Resiliency Engineering Framework for data collection and coding on Socio-Technical Systems as an interpretive lens, the study adopts a qualitative approach based on semi-structured interviews with 14 professionals across five organisations. The findings reveal a pronounced socio-technical imbalance: while technical measures centred on anticipate and withstand are comparatively established, the corresponding social factors – shared understanding, dedicated responsibility structures, and systematic learning – remain underdeveloped. These conditions are compounded by resource constraints and the absence of strategic prioritisation. Six exploratory hypotheses capture these patterns and offer empirically grounded starting points for future research on product-level cyber resilience.
Keywords: Cyber Resilience; Software Development Lifecycle; Qualitative Study; Cyber Resiliency Engineering Framework

„When does a man become a monster?“ Odysseus’ fluide Identität in Jorge Rivera-Herrans’ EPIC – The Musical - Peine, Sara (Wasser Wesen Wandel. Fluidität in (mehr-als-)literarischen Medien)

What is Participatory Digital Democracy? - Friesch, Kevin; Fuchs, Christian; Museba, Joel (The Communication Review)

Sportentwicklungsplanung - Meier, Heiko; Riedl, Lars; Kukuk, Marc (Grundwissen Sportsoziologie. Mit eLearning-Kurs)

Von Stilen, Quellen und Bildern - Siemoneit, Johannes Gabriel (Artes Renascentes)

Sitografia - Siemoneit, Johannes Gabriel (Artes Renascentes)

Rewiring the aging brain: exergaming modulates brain complexity in older adults - Piskin, Daghan Yüksel; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Frontiers in Aging Neuroscience)
Introduction Age-related changes in brain signal complexity are associated with cognitive decline and reduced neural adaptivity in older adults. Exergaming offers a promising prophylactic intervention combining physical and cognitive training. The aim of the present study was to assess how exergaming alters the temporal trajectory of brain signal complexity at rest and during gameplay in older adults. Methods Twenty-eight healthy older adults participated in a 4-week exergaming intervention. Electroencephalography was recorded using 64 electrodes at rest (pre- and post-intervention) and during exergaming (pre-, mid-, and post-intervention). Brain signal complexity was quantified using multiscale entropy across 64 time scales on preprocessed signals. Results Post-intervention resting-state analysis revealed significant reductions at fine and increases at coarse scales in frontal, central, and posterior entropy. During gameplay, entropy declined widespread by mid-intervention, particularly at coarse scales over frontal, central and temporal regions. From mid- to post-intervention, the decline narrowed leaving a net pre-to-post reduction concentrated at coarse scales in these regions. Discussion Resting-state changes indicated a shift toward a younger brain profile, characterized by a transition from age-related increases in local processing to enhanced distributed processing, which may potentially mitigate the rise in neural modularity associated with aging. During gameplay, brain signal complexity decreased in week 2, followed by a modest change by week 4, consistent with the framework in which complexity initially streamlines and then adjusts toward a task-specific optimum. These findings suggest that exergaming can beneficially modulate brain complexity in older adults, offering the potential to reduce age-related neural decline and support healthy brain aging.

Thermodynamic Properties of Tetramethoxysilane - Fiedler, F.; Baumhögger, Elmar; Kruse, Simon; Lemmon, E. W.; Kasper, Tina; Thol, M. (International Journal of Thermophysics)
Abstract A fundamental equation of state for tetramethoxysilane (TMOS) is developed based on the available experimental data. In addition, new density and speed of sound measurements were performed specifically for this work to improve the database. Owing to the limited overall data set, additional thermodynamic properties were analyzed to support the fitting procedure and ensure physically consistent behavior. Modified representations of thermodynamic properties that are typically employed in the fitting procedure were introduced to facilitate the application of constraints. The resulting model provides a consistent description of the thermodynamic properties of TMOS.

Vom Hühner-Holocaust über die Öko-Diktatur zum Kulturkampf um die Currywurst. Korpuslinguistische Perspektiven auf ernährungsbezogene Politisierungen - Markewitz, Friedrich; Wilk, Nicole M. (Zeitschrift für Literaturwissenschaft undLinguistik)

Brain complexity in motion: Multiscale entropy analysis on mobile EEG data to assess motor performance - Piskin, Daghan Yüksel; Cobani, Gjergji; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Brain Research Bulletin)

Zu Verbotenen Texten im Nationalsozialismus - Markewitz, Friedrich (Aptum. Zeitschrift für Sprachkritik und Sprachkultur)

Kommunikative Strategien im Umgang mit Macht und Ohnmacht im Getto Litzmannstadt - Markewitz, Friedrich (Macht und Partizipation in gesellschaftlichen Transformationsprozessen)

120 Tage im 'SS Experiment Love Camp'. Zu Genretropen und -kontroversen im Nazisploitationfilm - Markewitz, Friedrich (Pop-Zeitschrift)

Art the Clown goes to Hollywood. Wenn transgressives Genrekino Mainstream wird - Markewitz, Friedrich (Pop-Zeitschrift)

Hardness of approximation for ground state problems - Gharibian, Sevag; Hecht, Carsten (51st International Symposium on Mathematical Foundations of Computer Science (MFCS))
After nearly two decades of research, the question of a quantum PCP theorem for quantum Constraint Satisfaction Problems (CSPs) remains wide open. As a result, proving QMA-hardness of approximation for ground state energy estimation has remained elusive. Recently, it was shown [Bittel, Gharibian, Kliesch, CCC 2023] that a natural problem involving variational quantum circuits is QCMA-hard to approximate within ratio N^(1-eps) for any eps > 0 and N the input size. Unfortunately, this problem was not related to quantum CSPs, leaving the question of hardness of approximation for quantum CSPs open. In this work, we show that if instead of focusing on ground state energies, one considers computing properties of the ground space, QCMA-hardness of computing ground space properties can be shown. In particular, we show that it is (1) QCMA-complete within ratio N^(1-eps) to approximate the Ground State Connectivity problem (GSCON), and (2) QCMA-hard within the same ratio to estimate the amount of entanglement of a local Hamiltonian's ground state, denoted Ground State Entanglement (GSE). As a bonus, a simplification of our construction yields NP-completeness of approximation for a natural k-SAT reconfiguration problem, to be contrasted with the recent PCP-based PSPACE hardness of approximation results for a different definition of k-SAT reconfiguration [Karthik C.S. and Manurangsi, 2023, and Hirahara, Ohsaka, STOC 2024].

(Nicht)Nutzung von KI-Werkzeugen in der Lehre: ein Reflexionspapier - Rohlfing, Katharina J.; Steinhardt, Isabel; Scharlau, Ingrid; Schaper, Niclas; Holtfreter, Susan; Biere, Lea; Grimminger, Angela; Schmidt, Rebecca; Festner, Dagmar Franziska; Schmidt, Rebekka; Buhl, Heike M.; Mindt, Ilka; et al.

Ein Format zur handlungsnäheren Prüfung von Unterrichtsplanungskompetenz für das Lehramtsstudium im Fach Physik - Vogelsang, Christoph; Riese, Josef (Handlungsorientierung in der Ausbildung von Lehrkräften und pädagogischen Fachkräften. Konzeptionen und Forschungsperspektiven)

Towards Stakeholder-Aware Demand-Side management assessment in heterogeneous residential Microgrids: A Multi-Agent approach - Henne, Kevin; Rahlf, Henning Christoph; Naumann, Marius; Meschede, Henning (Energy Conversion and Management: X)
Expanding renewable energy sources is essential for a sustainable energy supply but challenges grid stability, as the volatility of solar and wind causes periods of over- and undersupply. Private households are central to this transition, combining dynamic consumption with decentralised generation. This paper presents a multi-agent microgrid simulation built on the Mesa framework, focusing on the heterogeneous objectives and technological capabilities of residential participants. Households are modelled as autonomous agents with individual strategies, while a dedicated “grid agent” represents the distribution system operator and regulates the microgrid in a grid-supportive manner. The emission factor serves as the key indicator for grid-friendly behaviour. Results show that in summer, unmanaged PV feed-in from heterogeneous households causes substantial grid stress and balancing effort for the distribution system operator. Dynamic electricity prices can incentivise grid-friendly dispatch, but their effectiveness depends on the correlation between price signals and renewable availability and cannot guarantee grid-supportive behaviour alone. The grid agent reliably improves the grid-supportive coefficient, yet its operating strategy, for instance additional peak-reduction objectives, can interfere with price-based incentives. Effective demand-side management therefore requires careful analysis of stakeholder interactions. Building on this insight, thepaper provides a basic framework for the design, implementation, and assessment of both integrated and individual energy management strategies within a microgrid environment. By simulating the dynamic interactions among system participants and strategies, it enables comprehensive evaluation of their collective impact on the grid, supporting the development of robust solutions for future electricity networks.
Keywords: Microgrid; Decentralised Energy Systems; Multi-Agent System; Residential Demand-Side Management; Optimisation